IMPACT OF TECHNOLOGY ON PHYSICAL ACTIVITY - Axtamov Djamshed Baxromovich (Western European Studies, 2024)
The rapid advancement of technology has brought about profound changes in various aspects of human life, including physical activity patterns. This article explores the impact of technology on physical activity levels and behaviors. It examines how modern technologies such as smartphones, social media, video games, and sedentary entertainment options influence individuals' engagement in physical activity. The article discusses both positive and negative effects, highlighting the potential of technology to promote active lifestyles through innovative solutions such as fitness apps, wearable devices, and virtual fitness classes. However, it also addresses concerns regarding the sedentary nature of many technological activities and their contribution to a more sedentary lifestyle. Strategies for leveraging technology to encourage physical activity and mitigate sedentary behavior are discussed, along with implications for public health and recommendations for future research
Keywords: Technology; physical activity; sedentary behavior; smartphones